A Statistical Model for Estimating Provision for Doubtful Debts - Budhathoki, Dhruba Kumar (Journal of Nepalese Business Studies, 2018)
This paper attempts to analyze a statistical model for estimating provision for doubtful debts based on available data and literature. Where a significant portion of an enterprise’s assets are tied up in Sundry Debtors (of any kind), the accuracy achieved in estimating this provision for doubtful debts assumes a special significance. This is very much well known to anyone who is seriously connected with financial matters, whether under any statute or for carrying out management accounting exercise. However, this paper is not intended to over-emphasize this aspect of financial management accounting. The purpose of this paper is to attempt to build a statistical model to enhance the degree of accuracy in this regard. The customary practice prevalent, at least in Nepal, is to estimate it mainly by applying a highly subjective judgmental process, bordering on a hunch-oriented process. The Journal of Nepalese Business Studies Vol. X No. 1 December 2017, Page: 78-84